Different Pain Level Of Diabetes Mellitus Patients With Peripheral Neuropathy Who Have Been Given Tens And Deep Breathing Interventions In Diabetic Foot Ulcer Treatment In Yogyakarta General Hospital - SATRIYA PRANATA (Fakultas Ilmu Keperawatan Universitas Islam Sultan Agung, Semarang, 2017)
Introduction : Regular intervention of diabetic foot ulcers is wound care. Patients often complain of pain when nurse performs wound care. If the pain is not resolved it will result in anxiety feeling. A routine intervention conducted so far is intra-breath in intervention to reduce pain, as it is expected by reducing the pain it will be followed by a decrease of patients’ anxiety. Intra-breath intervention has not been able to reduce pain quickly on a moderate scale, especially high-scale so it is necessary to find out other alternative interventions. The available comparative intervention is TENS. The purpose of this study is to know the difference between intra-breath and TENS intervention in the level of anxiety in diabetic patients with peripheral neuropathy in diabetic foot ulcer treatment. Method : This study used RCT method on 28 respondents divided into 14 intervention groups and 14 control groups. The anxiety of respondents was assessed using Hamilton Scale of Anxiety tools before and after conductin TENS intervention and intra-breath. TENS intervention was given for 15 minutes at a frequency of 100 Hz and intra-breath was given until the wound care intervention was completed. Result : The results showed that there was significant average difference of anxiety level between the use of TENS intervention and the use of intra-breath intervention in intervention group and the control group with value of P <0.05. TENS can reduce the level of anxiety with the value of P 0.000, while intra -breath is able to lower the level of anxiety with the value of P 0.006. Discussion : The respondents admitted the difficulty of experience maximum relaxation when wound care is done, this condition is related to the comfortable position of respondents. When wound care is done, the respondents can not relax maximaly because many of the foot that has ulcers should be padded with a pillow to maximize the treatment. Provision of TENS with a frecuency of 100 Hz is corresponding to the body’s bioelectricity, the patients that receive TENS intervention may become more rrelaxed with endorphine hormone release and decreasing of pain because the electricity blocks pain implans in the neural tube.